2019 14th ACM/IEEE International Conference on Human-Robot Interaction (HRI) 2019
DOI: 10.1109/hri.2019.8673116
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Human-Robot Proxemics Between Virtual Reality and the Real World

Abstract: Virtual Reality (VR) is gaining more and more popularity as a research tool in the field of Human-Robot Interaction (HRI). To fully deploy the potential of VR and benefit HRI studies, we need to establish the basic understanding of the relationship between the physical, real-world interaction (Live) and VR. This study compared Live and VR HRI with a focus on proxemics, as proxemics preference can reflect comprehensive human intuition, making it suitable to be used to compare Live and VR. To evaluate the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…For example, before talking with another person, people adjust their position relationships based on personal space (Hall, 1966). Many social robots also consider such position relationships before interacting with people as preconversational interactions (Obaid et al, 2016;Li et al, 2019;Saunderson and Nejat, 2019). Following such concepts, robotics researchers investigated the pre-touch reaction distance around a face between people and reported that the average distance is about 20 cm (Shiomi et al, 2018).…”
Section: Technical Challenges For Touch Interactionmentioning
confidence: 99%
“…For example, before talking with another person, people adjust their position relationships based on personal space (Hall, 1966). Many social robots also consider such position relationships before interacting with people as preconversational interactions (Obaid et al, 2016;Li et al, 2019;Saunderson and Nejat, 2019). Following such concepts, robotics researchers investigated the pre-touch reaction distance around a face between people and reported that the average distance is about 20 cm (Shiomi et al, 2018).…”
Section: Technical Challenges For Touch Interactionmentioning
confidence: 99%
“…Because human perception differs in many aspects between actual reality and VR, we cannot simply replace the experimental environment with VR (Wijnen et al, 2020). Therefore, it is necessary to consider several conditions, such as differences in distance perception (Li et al, 2019), gaze control (Duchowski et al, 2014;Sidenmark and Gellersen, 2019), and visual perception owing to a narrow field of view (Willemsen et al, 2009;Mizuchi and Inamura, 2018).…”
Section: Provision Of a Uniform Experimental Condition For Participantsmentioning
confidence: 99%
“…Such comparisons have been done for many different studies: locomotion toward a goal [1,8], collision avoidance [1,5,16,30], personal space [19,28], etc. Also, HRI experiments in VR in [23] explore the bias when the human only is immersed in VR. All these studies show that, while there is some quantitative differences, such as slower walking speed or bigger personal space, humans display similar patterns and behaviors in VR.…”
Section: Virtual Reality For Robotics and Behavioral Experimentsmentioning
confidence: 99%
“…To the best of our knowledge, this is the first time that a real robot is immersed in VR in order to make it capable of operating in a real or a virtual environment in the same way. In the closest work to our [23], the robot and the human positions are tracked based on HTC vive trackers for them to share their mutual position, the robot is not perceiving the human position through its sensors, and the tracking is a low dimensional one (the posture of the human and of the robot are ignored). The robot has direct access to its externally tracked position, thus not dealing with the robot sensing and processing capacities issues.…”
Section: Virtual Reality For Robotics and Behavioral Experimentsmentioning
confidence: 99%